Utilization of Information Technology in Promoting Slumpring Tourism in Cemaka Bumijawa Village - tulodo, Rizki Prasetyo Tulodo; Agus Wibowo; Nur Tulus Ujianto (Universitas Pancasakti Tegal, 2023)
The development of the tourism sector has had a positive impact on economic development and local people's livelihoods. One type of tourism that has developed quite rapidly in recent years in Indonesia is a tourist village. Slumpring Tourism in Cempaka Village, Bumijawa has quite a lot of tourism potential, but it has not been optimally developed. Various aspects of the tourism business have been developed by the government and tourism actors to increase revenue in this sector. However, the current problem is that the existing tourism potential has not been mapped properly, and the use of Information Technology (IT) has not been optimal, especially the use of social media in tourism promotion. Therefore, in this community service activity, community involvement is carried out in mapping tourism potential, IT utilization training that emphasizes promotion through social media, as well as making a master plan as a basis for tourism development. The results of this activity are the mapping of tourism potential, information technology training and the creation of a master plan for the development of Slumpring tourism in Cempaka Bumijawa Village.